Geliat Budaya: Film Dokumenter Suku Lakota Life Lakota - Sukarni Suryaningsih (Endogami: Jurnal Ilmiah Kajian Antropologi, 2021)
The Lakota people are an important part of the Sioux tribe whose existence has made history for the development of the diversity of the United States' multicultural society. Most of the history of the tribes in the state of South Dakota reflects the powerlessness of the exploitation of European immigrants who later became the United States federal government. This study intends to look at the condition of the Lakota people in the past and in the present, especially the efforts they take to maintain their cultural identity in the midst of all the difficulties of living in the reservation area. Through qualitative research using a literature review model, this research data comes from the Life Lakota documentary film and also written sources that review the Lakota tribal community. The results show that the efforts made by the Sioux YMCA organization through Marrowbone activities that provide cultural assistance to Lakota children and youth are aimed at bringing the tribal kinship relations closer and bringing them closer to the ancestral traditions of the Lakota tribe through joining camping activities, exercising rodeo and learning native Lakota language.